LONG-TERM USE OF BENZODIAZEPINES IN PATIENTS WITH AND WITHOUT PERSONALITY DISORDERS - Žikić, Olivera; Kostić, Jelena; Stojanov, Jelena; Binić, Iva; Nikolić, Gordana (Acta medicae Medianae, 2025)
Personality disorders (PD) are prevalent co-morbid conditions among addicted individuals. Our study aimed to determine whether long-term, continuous use of benzodiazepines (over a year) leads to the development of symptoms of dependence considering the presence or absence of personality disorders. The group consisted of 78 benzodiazepine users who used benzodiazepine as a monotherapy for at least 1 year before a screening. Patients completed a group of questionnaires: a semi-structured questionnaire for sociodemographic data as well as for basic data on the use of benzodiazepines, Wisconsin Personality Inventory, and Benzodiazepine Dependence Self-Report Questionnaire. The group was divided into two subgroups: the group of subjects with personality disorders (60.26%) and those without personality disorders (39.74%). These two groups were mutually compared concerning: (a) correlates of benzodiazepine dependence (problematic use of benzodiazepines, preoccupation with benzodiazepines, lack of compliance, and withdrawal syndrome) and (b) intensity of benzodiazepine dependence. In the whole group, approximately 70% of subjects had positive indicators for physical dependence (lack of compliance due to a rise of tolerance in 73.08% and withdrawal in 70.51% of subjects). The psychological dependence indicator (preoccupation with benzodiazepines) was positive in 94.87% of subjects, as well as for social aspects of dependence (problematic use of BDZs) in 93.59%. The total score, or intensity of benzodiazepine dependence, was statistically higher in the group with personality disorder. Patients with a personality disorder had more frequent and more intensive preoccupation with benzodiazepine and lack of compliance. Co-occurrence of two or more personality disorders increases the intensity of preoccupation with a benzodiazepine.
Keywords: benzodiazepine, dependence, personality, withdrawal